Complex Macromolecular Systems II - Müller, Axel H. E.; Schmidt, Hans-Werner (Advances in Polymer Science, 2010)
-Polyelectrolyte Stars and Cylindrical Brushes By Y. Xu, F. Plamper, M. Ballauff, and A. H. E. Müller -Various Aspects of the Interfacial Self-Assembly of Nanoparticles By N. Popp, S. Kutuzov, A. Böker -Holographic Gratings and Data Storage in Azobenzene-Containing Block Copolymers and Molecular Glasses By H. Audorff, K. Kreger, R. Walker, D. Haarer, L. Kador, and H.-W. Schmidt -Donor-Acceptor Block Copolymers with Nanoscale Morphology for Photovoltaic Applications By M. Sommer, S. Huettner, and M. Thelakkat -Recent Advances in the Improvement of Polymer Electret Films By D. P. Erhard, D. Lovera, C. von Salis-Soglio, R. Giesa, V. Altstädt, and H.-W. Schmidt.